2015
DOI: 10.2217/nnm.15.133
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties Affect the Synthesis, Controlled Delivery, Degradation and Pharmacokinetics of Inorganic Nanoporous Materials

Abstract: Controlling size, shape and uniformity of porous constructs remains a major focus of the development of porous materials. Over the past two decades, we have seen significant developments in the fabrication of new, porous-ordered structures using a wide range of materials, resulting in properties well beyond their traditional use. Porous materials have been considered appealing, due to attractive properties such as pore size length, morphology and surface chemistry. Furthermore, their utilization within the lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 174 publications
(209 reference statements)
0
11
0
Order By: Relevance
“…This information allowed for generating a database repository to predict nanocarrier toxicity. Synthetic nanoparticles [32][33][34][35] have demonstrated promising applications in therapeutic delivery; however, these efforts are often jeopardized due to a lack of standard procedures designed to investigate the biological impact. [36] Similarly, more recent efforts designed to take inspiration from nature to develop biomimetic delivery systems [37][38][39][40][41] have also been affected by a lack of standardized techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This information allowed for generating a database repository to predict nanocarrier toxicity. Synthetic nanoparticles [32][33][34][35] have demonstrated promising applications in therapeutic delivery; however, these efforts are often jeopardized due to a lack of standard procedures designed to investigate the biological impact. [36] Similarly, more recent efforts designed to take inspiration from nature to develop biomimetic delivery systems [37][38][39][40][41] have also been affected by a lack of standardized techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the advantages first-generation nanoparticles provide [ 55 , 56 ], the many biological obstacles they are required to overcome have led to the development of several delivery vectors designed to decouple the multitude of tasks required to bypass these barriers [ 57 , 58 , 59 ]. Previously, our group introduced multistage nanovectors (MSV) [ 60 , 61 ], engineered to systemically shield, transport and reliably deliver therapeutic and imaging agents, thereby making them ideal for theranostics applications [ 62 , 63 ].…”
Section: Multistage Nanovectorsmentioning
confidence: 99%
“…Previously, our group introduced multistage nanovectors (MSV) [ 60 , 61 ], engineered to systemically shield, transport and reliably deliver therapeutic and imaging agents, thereby making them ideal for theranostics applications [ 62 , 63 ]. Designed using porous silicon due to its biocompatibility and degradability [ 64 , 65 ], well-established fabrication techniques make it possible to uniquely control parameters such as shape, size, and porosity that can aid in the strategic negotiation of biological barriers [ 56 , 57 , 66 ]. As one example, mathematical modeling has revealed that MSV exhibit superior margination and adhesion during systemic circulation, favoring the release of a payload into the extracellular space [ 67 , 68 ].…”
Section: Multistage Nanovectorsmentioning
confidence: 99%
“…Other groups have explored porous materials, to encapsulate and deliver nanoparticles, which provide space to attach additional targeting moieties, enabling greater tissue penetration [26]. For example, porous silicon has been widely investigated for its biodegradability and biocompatibility [2729].…”
Section: Significance and Overview Of Nanotechnologymentioning
confidence: 99%